ANALISIS KUALITAS PELAYANAN ELEKTRONIK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN (Studi pada Pelanggan Erigo Store di Surakarta) - Achmad Muchtaris; Zulfa Irawati (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the influence of Electronic Service Quality and Brand Image on Customer Loyalty, with Customer Satisfaction as a mediating variable, among customers of Erigo Store in Surakarta. The research is motivated by the increasingly competitive fashion industry and the importance of building customer loyalty through digital services and a strong brand image. A quantitative approach was employed, using a survey method with 130 respondents selected through purposive sampling. Data were collected via an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 3.2 software. The results show that Electronic Service Quality and Brand Image have a positive and significant effect on both Customer Satisfaction and Customer Loyalty. Additionally, Customer Satisfaction significantly influences Customer Loyalty. The findings further reveal that Customer Satisfaction mediates the relationship between Electronic Service Quality and Brand Image on Customer Loyalty. These results highlight the critical role of digital service and brand perception in shaping satisfaction and loyalty in the modern fashion business context.